Labor Migration from Third Countries to Swedish Low-wage Jobs - Frödin, Olle; Kjellberg, Anders (Nordic Journal of Working Life Studies, 2018)
Since December 2008, Sweden has more liberal rules for labor immigration from ‘third countries’ – countries outside the European Union (EU) and European Economic Area (EEA) – than any other country in the Organisation for Economic Co-operation and Development (OECD). The introduction of employer-driven labor immigration, motivated by the need to address labor shortages, resulted in large inflows of migrants in low-skilled occupations in labor surplus sectors. This article examines the situation of the approximately 500 restaurant and cleaning workers who were granted work permits in Stockholm in 2012. More than four out of ten labor migrants ‘switched track’ from asylum seekers, students, or family connection. Every second worker was recruited to companies without collective agreements. In several cases, a nationality/ethnic link between migrant and employer appears to exist. The reasons why so many low-skilled labor migrants in nonseasonal occupations were recruited are discussed. Finally, alternative explanations for the decline of this type of labor migration after 2011 are considered.